Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd004526.pub2
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium supplementation on bone loss in postmenopausal women

Abstract: Calcium supplementation alone has a small positive effect on bone density. The data show a trend toward reduction in vertebral fractures, but it is unclear if calcium reduces the incidence of non vertebral fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 28 publications
1
46
0
5
Order By: Relevance
“…Studies were excluded if participants had undergone bariatric surgery or were taking medications designed to induce weight loss. Studies were also excluded if the intervention involved calcium supplementation or supervised exercise, or if exercise was the primary means of eliciting weight loss, because of potential confounding effects of calcium supplementation (35,56) or physical activity on bone mass. (57) Because physical activity is frequently recommended for weight management, to reduce publication bias we included interventions in which exercise was recommended as part of a healthier lifestyle, provided that the exercise was not supervised or was not the primary focus of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Studies were excluded if participants had undergone bariatric surgery or were taking medications designed to induce weight loss. Studies were also excluded if the intervention involved calcium supplementation or supervised exercise, or if exercise was the primary means of eliciting weight loss, because of potential confounding effects of calcium supplementation (35,56) or physical activity on bone mass. (57) Because physical activity is frequently recommended for weight management, to reduce publication bias we included interventions in which exercise was recommended as part of a healthier lifestyle, provided that the exercise was not supervised or was not the primary focus of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the effects of diet, the balanced ingestion of calcium (8,9)/vitamin D (10)/vitamin K (11) is recommended by the "Japanese 2015 Guidelines for Prevention and Treatment of Osteoporosis" (1), and several studies have reported that it increases BMD, thereby preventing fractures (12)(13)(14). In the intervention performed in the present study, a leaflet was delivered to visually promote understanding, and guidance through detailed explanations was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Увеличение экскреции кальция в суточной моче при лечении препаратом Кальций-Д 3 Никомед форте, указы-вающее на повышение объема всасывания кальция в ЖКТ [17], и нормализация уровня ПТГ свидетельствуют об устранении кальциевого дефицита при лечении препара-тами Кальций-Д 3 Никомед и Кальций-Д 3 Никомед форте. По данным многих авторов, назначение комбинированной терапии кальцием и витамином D приводит к снижению уровня биохимических маркеров костной резорбции [3,15].…”
Section: Discussionunclassified